(untitled) (Research, Society and Development, 2022)
This study describes the stages of structuring and validating a didactic game, with the purpose of promoting learning about oral health in schoolchildren, encouraging the practice of toothbrushing and providing guidance on cariogenic and non-cariogenic foods. The game’s development was based on the CTM3 method and the error-free learning methodology. It is a board-type game, in the shape of a mouth, with 32 spaces that assumed the shape of teeth. To validate the game, two instruments were filled out by specialists with a PhD in the areas of education or health, and experience in the production of educational and didactic materials. Experts validated the game and suggested some improvements in certain instructions to students, such as: better specifying the behaviors that should be emitted by children and adapting certain visual representations. The suggested adjustments were made and the game was subsequently validated by the defense panel of a Professional Master’s Program at a Higher Education Institution in Alagoas. Thus, the game was structured and validated to help teachers work on the topic of oral health in the school environment. As this is a fun and attractive process, it is expected to awaken in children who will use the game, the desire to perform their oral hygiene and, in teachers, an interest in introducing the topic of oral health in their teaching activities.